Long-term domiciliary oxygen therapy in cor pulmonale complicating chronic bronchitis and emphysema. Issue 4 (August 1976) - Leggett, R J; Cooke, N J; Clancy, L; Leitch, A G; Kirby, B J; Flenley, D C
Abstract : Ten patients with cor pulmonale complicating severe chronic bronchitis and emphysema have been treated with 2 litres/min of oxygen for prolonged periods in the day, at home, over 12 to 62 months. Two patients died after 12 and 36 months of treatment. Pulmonary arterial pressure was reduced in seven patients, and red cell mass in eight, when the oxygen was given for over 15 hours in the day. Hospital inpatient treatment was greatly reduced following the start of long-term oxygen treatment in all patients. This treatment is expensive, and a controlled trial is necessary to establish its definitive place and cost-effectiveness, but the results of such a current Medical Research Council trial will not be available for a further two years.